2008
DOI: 10.1021/ar7002336
|View full text |Cite
|
Sign up to set email alerts
|

A Combinatorial Polymer Library Approach Yields Insight into Nonviral Gene Delivery

Abstract: CONSPECTUSThe potential of gene therapy to benefit human health is tremendous because almost all human diseases have a genetic component, from untreatable monogenic disorders to cancer and heart disease. Unfortunately, a method for gene therapy that is both effective and safe has remained elusive. It has been said that "there are only three problems in gene therapy -delivery, delivery, and delivery." (quote from I. M. Verma in Jaroff, L. TIME, 1999; Jan 11).This Account describes an alternative strategy to vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
516
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 539 publications
(532 citation statements)
references
References 43 publications
(148 reference statements)
14
516
0
2
Order By: Relevance
“…It is suggested that positively charged nanoparticles are generally taken up into the cells through endocytosis mechanism. 33 Our TEM experiments also support a similar mechanism and the high transfection of RSV-F gene via PCNSs, due to the high endocytosis efficiency of PCNSs (through cell membranes).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…It is suggested that positively charged nanoparticles are generally taken up into the cells through endocytosis mechanism. 33 Our TEM experiments also support a similar mechanism and the high transfection of RSV-F gene via PCNSs, due to the high endocytosis efficiency of PCNSs (through cell membranes).…”
Section: Discussionsupporting
confidence: 77%
“…Since the cells could not be cultured beyond a few days, we could 33 showed identical result in Cos-7 cells. The superior transfection capability of PCNSs may be attributed to the cationic nature of chitosan shell that can interact with negatively charged cell membranes, allowing it to be taken up by cells via endocytosis.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…PEAs were synthesized as previously reported. 34,37,38 Briefly, one diacrylate backbone monomer (B) was mixed with one amine-containing sidechain (S) at 1.2:1 or 1.05:1 ratio and stirred overnight at 90°C. Acrylate-terminated B-S base polymers resulted from Michael addition of amines to the acrylate groups.…”
Section: Polymer Synthesismentioning
confidence: 99%
“…Natural and synthetic cationic polymers have been previously studied because they are potentially safer and easier to manufacture, 27,28 but nondegradable polymers like poly(ethyleneimine) suffer from high toxicity, 29 which correlates with high molecular weight. 30 Although polymeric gene delivery has been traditionally less efficient than virusmediated gene transfer, 31 members of one class of polymers, ie, poly(ester amine)s, have been found to be very effective in DNA delivery to a number of cell types while causing less toxicity than leading commercially available transfection reagents, [32][33][34] likely due to the ability of polymers to degrade under physiological conditions and their theoretically unlimited variation in structure and properties, providing the flexibility to choose a polymer structure based on the particular purpose for which it is best suited.…”
Section: Introductionmentioning
confidence: 99%